2014
DOI: 10.17721/2227-1481.4.42-45
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic filament detection with a layer smoothing method

Abstract: Filaments are clearly visible in galaxy distributions, but they are hardly detected by computer algorithms. Most methods of filament detection can be used only with numerical simulations of a large-scale structure. New simple and effective methods for the real filament detection should be developed. The method of a smoothed galaxy density field was applied in this work to SDSS data of galaxy positions. Five concentric radial layers of 100 Mpc are appropriate for filaments detection. Two methods were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Figure 2: Sky distribution of SDSS galaxies with radial velocities between 4000 and 11000 km/s. Larger dots are faint X-ray galaxies, squares -bright X-ray galaxies with F X > 3.7 · 10 −13 erg/cm 2 , rectangles -filaments from [1], double squares -galaxies in filaments which were considered in [4]. Figure 3: Example of new X-ray spectrum of Seyfert galaxy in SDSS filament: 2MASX J15585579+0248338.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2: Sky distribution of SDSS galaxies with radial velocities between 4000 and 11000 km/s. Larger dots are faint X-ray galaxies, squares -bright X-ray galaxies with F X > 3.7 · 10 −13 erg/cm 2 , rectangles -filaments from [1], double squares -galaxies in filaments which were considered in [4]. Figure 3: Example of new X-ray spectrum of Seyfert galaxy in SDSS filament: 2MASX J15585579+0248338.…”
Section: Discussionmentioning
confidence: 99%
“…In [2] it was shown that extragalactic X-ray sources are AGNs and clusters. It was also shown in [4] that the main type of X-ray galaxies is Seyfert 1. X-ray spectra of 42 Seyfert 1 galaxies from SDSS region were analysed in [5].…”
Section: Introductionmentioning
confidence: 87%
“…Завдання чисельного N -вимiрного i гiдродинамiчного космологiчного моделювання є досить складними. Важко порiвнювати результати моделювання зi спостережними даними через великi систематичнi похибки [5]. Метою даної роботи було змоделювати поточний великомасштабний розподiл галактик випадковими гаусiвськими полями.…”
Section: алгоритм генерацIї випадкових розподIлiвunclassified
“…Hennebelle et al [12] showed a method based on adaptive mesh refinement magneto hydrodynamic simulations, which treat self-consistently cooling and selfgravity. Tugay [13] proposed a layer smoothing method, 2 Advances in Astronomy which described cellular large-scale structure of the universe (LSS) as a grid of clusters with density larger than a limited value, to detect extragalactic filaments. Men'shchikov [14] proposed a multi-scale filaments extraction method named getfilaments, which decomposed a simulated astronomical image containing filaments into spatial images at different scales to prevent interaction influence of different spatial scale structures.…”
Section: Introductionmentioning
confidence: 99%